Creating Educational Solutions for Optimizing Learning Factory Operations and Outcomes - Henry; Sarah Brown; Jack Jones (International Transactions on Education Technology (ITEE), 2025)
The rapid development of industrial education has prompted a growing need for effective Learning Factory (LF) management systems that integrate educational principles with industrial practices. This paper investigates the development of educational information systems tailored to optimize learning factory operations. The study aims to design an innovative information system and e-learning platform that streamlines the operational management of learning factories, ensuring effective resource allocation and maximizing the educational value of these settings. A mixed-methods approach, combining qualitative interviews with industry experts and quantitative surveys from educational institutions, was used to gather data on the needs and effectiveness of current management tools. Additionally, a prototype system was developed using agile software development methodologies. The findings reveal that the proposed system significantly improves the management of resources, enhances the learning experience, and bridges the gap between theoretical education and practical industrial applications. Moreover, the e-learning platform supports continuous knowledge transfer and facilitates real-time decision-making in the factory environment. The study concludes that the integration of tailored information systems and e-learning platforms in learning factories not only optimizes operational efficiency but also enriches the educational outcomes for students. This research offers valuable insights for educational institutions and industries aiming to align their training programs with the latest industrial advancements.